Custodial reindeer and custodial goats - part of reindeer herding and animal husbandry - Evjen, Bjørg (Rangifer, 2007)
Source at https://doi.org/10.7557/2.27.2.162. The Sami husbandry has traditionally incorporated reindeer, which did not belong to the nomadic household. According to the national census from 1875, this system was found in many parts of Norway. Among the counties, Nordland stood out having the highest number of households owing custodial reindeer. Most of the households were non-Sami, and most of them having less than ten reindeer. Especially in Nordland and Troms, a system with custodial goats also served as the transaction. There were eventually, with an exception of Finnmark, rules in place trying to prevent settled people from keeping reindeer, only followed in part. The system went on till after the Second World War, mainly because it was an important part of the household economy of the settled people. The great changes and rational- ization within the agricultural sector, the growth of industrial society, and the modernisation of society in general under- mined the use of reindeer as a part of the household livestock.